2020
DOI: 10.12669/pjms.36.5.2476
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cell free mitochondrial DNA as a biomarker of disease severity in different viral infections

Abstract: Objective: Cell Free mitochondrial DNA (CF mt-DNA) has emerged as a novel biomarker to investigate disease pathophysiology of different infections. The present study was designed to elucidate the association between CF mt-DNA, IL-6 and viral load in HIV, HBV and HCV infections and predict its role as a potential biomarker to assess the disease severity in viral infections. Methods: Total 120 blood samples were collected from January 2018 to December 2018 of HIV, HBV and HCV patients and healthy controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…mtDNA plasma levels were significantly higher in patients with acute HIV infection and late presenters than in healthy individuals or in long-term non-progressors [ 194 ]. Ali et al [ 193 ] found a seven-fold increase in the level of cfDNA in the serum of HIV-infected individuals. In contrast, Lauring et al [ 195 ] did not find any association between plasma mtDNA and HIV disease state; however, they noted the small sample size as a limitation of their study.…”
Section: Cell-free Dna In Hiv Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…mtDNA plasma levels were significantly higher in patients with acute HIV infection and late presenters than in healthy individuals or in long-term non-progressors [ 194 ]. Ali et al [ 193 ] found a seven-fold increase in the level of cfDNA in the serum of HIV-infected individuals. In contrast, Lauring et al [ 195 ] did not find any association between plasma mtDNA and HIV disease state; however, they noted the small sample size as a limitation of their study.…”
Section: Cell-free Dna In Hiv Infectionmentioning
confidence: 99%
“…Data obtained in different virus-mediated diseases, including HIV, indicate that EV-based mechanisms can impact viral pathogenicity, facilitate viral spread, and modulate antiviral immune responses [ 63 , 193 , 194 , 201 , 202 ]. Lee [ 203 ] provides a comprehensive summary of the potential roles of Evs in HIV-1 infection.…”
Section: Cell-free Dna In Hiv Infectionmentioning
confidence: 99%
“… 9 It is also known that mitochondria is the main organelle involved in the initiation of intrinsic pathway of apoptosis. 10 , 11 This direct effect of melatonin on mitochondria may be the reason for its anti-apoptotic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The timely provision of ART ensures appropriate management of opportunistic infections, preventing secondary transmission and associated complications 6 , leading to improved health and prolonging the life expectancy among the people living with HIV. 7,8 Though it is highly recommended to initiate the therapy before the infection begins, the delayed or interrupted HIV treatment initiations has been widely observed in developed and developing countries. 9 The treatment onset and compliance vary with respect to culture and traditions worldwide.…”
Section: Introductionmentioning
confidence: 99%